Structural and Optical Properties of In2S3 Thin Films Prepared by Flash Evaporation - K. Bouabid; A. Ihlal; A. Outzourhit; E. L. Ameziane (Active and Passive Electronic Components)
In2S3thin films were deposited by flash evaporation of In2S3 powder. The effect of annealing in vacuum and under sulphur atmosphere on the structural and optical properties of these films was investigated. X-ray diffraction studies reveal that the as-deposited films are amorphous. The formation of β-In2S3 phase is obtained after annealing under vacuum at 693 K. Heat treatments under sulphur pressure lead to the formation of the above phase at a less annealing temperature (573 K). The energy dispersive X-ray (EDX) analysis reveals that the sulphurized films are nearly stoichiometric and those annealed in vacuum are sulphur deficient. Optical transmission spectra showed a slight shift of the absorption edge towards lower wavelengths. The optical gap value varied between 2.4 and 3 eV as a function of the film thickness and the annealing temperature.